Antonin Artaud: uma breve análise da emissão radiofônica “Para acabar com o juízo de Deus” (Olhares, 2020)
This article makes a brief analysis of the work To End God’s Judgment, highlighting historical aspects of the context in which Antonin Artaud is located and biographical characteristics that differentiated his artistic production.
Keywords: Antonin Artaud; To End God’s Judgment; Theater of Cruelty